Inventory of Melastomataceae In Mountain Sibutan Nagalingga Village Brand District District Karo Province of North Sumatra - Siti Khodijah S, Husnarika Febriani, Melfa Aisyah Hutasuhut (Pusdikra-Publishing.com, 2023)
Plant inventory is an exertion to group data or classify a type of factory that exists in an area. This study aimed to identify plants in the Melastomateceae family and determine the characteristics of plant species based on the key determination of the Melastomataceae family found in Sibuatan Mount Nagalingga Village Merek Dictrict Karo Regency North Sumatra Province. This research was conducted from January 2021 to September 2021. The research method used a qualitative descriptive method by exploratory observations along the path starting from the jungle door, shalter 1, shalter 2, to shalter 3. The data analysis was descriptive analysis qualitative. Based on the results of the inventory, 15 specieses of the Melastomaceae family were obtained : Dissochaeta macrosepala Staf., Medinila alpestris (Jack) Bl., Medinilla beamanii J. C. Regalado., Medinilla ridleyi Merr., Melastoma malabathricum L., Melastoma sp. 1, Melastoma sp. 2, Memecylon sp. 1 , Memecylon sp. 2, Miconia appendiculata Triana,. Miconia laevigata (L.) DC. , Phyllagathis griffthii (Hook. Fil. Ex Teriana) King., Pternandra sp., Sonerila heterophylla Jack., and Sonerila tenuifolia Bl. The characteristics of the Melastomatacea family are mountaintop ornamental plants with leaves that have three veins that curve upwards, striking flowers and berry-shaped fruit (round).